The Effect Of Digital Wallets And E-Money On The Consumption Spending Patterns Of Generation Z In Bengkulu City - Wardani, Desta Andriani Kusuma; Soleh , Ahmad; Fitriano , Yun (Jurnal Pusat Manajemen, 2025)
This research aims to determine the effect of Digital Wallets and E-Money on the consumption spending patterns of Generation Z in Bengkulu City. This study uses a quantitative descriptive and verificative method with 70 respondents selected through a purposive sampling technique. Data were collected using questionnaires and analyzed using SPSS version 22 through several tests, including validity, reliability, multiple linear regression, t-test, F-test, and coefficient of determination (R²).The results show that Digital Wallet and E-Money have a positive and significant effect on consumption spending patterns. The Digital Wallet variable has a t-value of 3.749 with a significance value of 0.000, while the E-Money variable has a t-value of 2.735 with a significance value of 0.008. Simultaneously, both variables significantly influence consumption spending patterns with an F-value of 54.281 and a significance value of 0.000. The coefficient of determination (R²) is 0.618, indicating that Digital Wallet and E-Money explain 61.8% of the variation in consumption spending patterns, while the remaining 38.2% is influenced by other factors.